Connections between serum Trimethylamine N-Oxide (TMAO), a gut-derived metabolite, and vascular biomarkers evaluating arterial stiffness and subclinical atherosclerosis in children with obesity - Mihuta, Monica Simina; Paul, Corina; Borlea, Andreea; Roi, Cristina Mihaela; Pescari, Denisa; Velea-Barta, Oana-Alexandra; Mozos, Ioana; Stoian, Dana (Frontiers in Endocrinology, 2023)
Introduction Childhood obesity leads to early subclinical atherosclerosis and arterial stiffness. Studying biomarkers like trimethylamine N-oxide (TMAO), linked to cardio-metabolic disorders in adults, is crucial to prevent long-term cardiovascular issues. Methods The study involved 70 children aged 4 to 18 (50 obese, 20 normal-weight). Clinical examination included BMI, waist measurements, puberty stage, the presence of acanthosis nigricans, and irregular menstrual cycles. Subclinical atherosclerosis was assessed by measuring the carotid intima-media thickness (CIMT), and the arterial stiffness was evaluated through surrogate markers like the pulse wave velocity (PWV), augmentation index (AIx), and peripheral and central blood pressures. The blood biomarkers included determining the values of TMAO, HOMA-IR, and other usual biomarkers investigating metabolism. Results The study detected significantly elevated levels of TMAO in obese children compared to controls. TMAO presented positive correlations to BMI, waist circumference and waist-to-height ratio and was also observed as an independent predictor of all three parameters. Significant correlations were observed between TMAO and vascular markers such as CIMT, PWV, and peripheral BP levels. TMAO independently predicts CIMT, PWV, peripheral BP, and central SBP levels, even after adding BMI, waist circumference, waist-to-height ratio, puberty development and age in the regression model. Obese children with high HOMA-IR presented a greater weight excess and significantly higher vascular markers, but TMAO levels did not differ significantly from the obese with HOMA-IR<cut-offs. TMAO did not correlate to HOMA-IR and insulin levels but presented a negative correlation to fasting glucose levels. An increase in TMAO was shown to be associated with an increase in the probability of the presence of acanthosis nigricans. TMAO levels are not influenced by other blood biomarkers. Conclusion Our study provides compelling evidence supporting the link between serum TMAO, obesity, and vascular damage in children. These findings highlight the importance of further research to unravel the underlying mechanisms of this connection.